COMPUTER SIMULATION OF MODERN AIRCRAFTS BY USING NETWORK TECHNOLOGIES OF REMOTE CONTROL - Pavlov, Vadym; Volkov, Oleksandr; Voloshenyuk, Dmytro (Proceedings of National Aviation University (archive), 2014)
The problem of a computer simulation of modern aircraft and the use of new models and remote aircraft control (through the networks) to improve safety, especially in difficult circumstances and in conflict situations is considered in the paper